Vira Diachuk: VERBALIZATION OF THE CONCEPT MOTHER IN MIDDLE-UPPER-DNIEPER AND HUTSUL DIALECTS: AN ATTEMPT TO COMPARE - Diachuk, Vira (Linguistic Bulletin (Movoznavchyi Visnyk), 2022)
Аbstract. Introduction. In the national worldview system, concepts occupy an important place because they indicate the community value attitude to the cultural phenomenon. Verbalization of the concept testify to its significance in the speaker’s world-image and show culturally determined ideas about it. In this regard, the study of concepts remains an important and urgent task of linguistics. Purpose. The aim of our research is to find out the common cognitive features of the concept MOTHER and ways of its verbalization in the Middel-upper-Dnieper and Hutsul dialects. Results. The concept MOTHER has six common cognitive features in researced linguistic areas: pregnancy causes changes in the woman’s body; childbirth turns a woman into a mother; a mother is the most relative person for the baby; a mother takes care of the baby; a mother is the first child’s educator; a mother is a child’s defender. In general, the concept MOTHER is represented by lexical and syntactic ways. Lexical ways of verbalization in the Middle-upper-Dnieper dialects are single nouns, noun derivatives, dialect verb, single metaphorical nominations. Syntactic nominations are illustrated by phrases (descriptive, possessive), compound formations with the apositive connection between their components, constructions with the form of «respectable plurality», phraseological units and comparative constuctions. The lexical ways of verbalization in the Hutsul dialects are also represented by single nouns, noun and verbal derivatives, single metaphorical nominations. Syntactic verbalization ways include verbal, descriptive, possessive units, comparative constuctions, phraseological units and constructions with the form of «respectable plurality». Originality. The concept MOTHER has not been the object of research in the Middle-upperDnieper and Hutsul dialects yet, so the investigation of its cognitive features and ways of verbalization is the advances of this article. Conclusions. In spite of the fact, that the researched linguistic areas are far from each other and belong to different archetypes of local culture, different ways of the concept verbalization testify to its important place in dialect speakers’ conceptual world pictures. Ways of the concept verbalization focus around lexical item «mother», its different variants and relate to the names of a woman during the period of pregnancy and after childbirth. Common nominative, semantic and evaluative features of compared linguistic and cultural areas indicate the closeness of their traditions and at the same time a high level of their uniqueness.